Epidemiology and characterization of Staphylococcus epidermidis isolates from humans, raw bovine milk and a dairy plant - Jaglic, Z; Michu, E; Holasova, M; Vlkova, H; Babak, V; Kolar, M; Bardon, J; Schlegelova, J (Epidemiology and infection, 2010)
Geographically related Staphylococcus epidermidis isolates from human patients (n=30), dairy farms (farmers and individual raw milk from cattle, n=36) and a dairy plant (n=55) were examined for epidemiological relatedness by pulsed-field gel electrophoresis and, using in vitro methods, for the ability to produce biofilm and antimicrobial resistance. Methicillin-resistant isolates (MRSE) were also identified and characterized. Isolates from farmers and dairy cattle were found to be genetically related, while isolates from human patients were highly diverse. Some dairy plant isolates (18.2%) were closely related to those from dairy farms. Biofilm production and resistance to antimicrobial agents were most typical for isolates from human patients, of which 76.7% were MRSE. Methicillin resistance was also widespread in farm-related isolates (61.1%). This study indicates the possible transmission of S. epidermidis between cattle and farmers. Dairy products were not proven to be an important source of either human infections or methicillin-resistant strains.
Keywords: Microbial Sensitivity Tests; DNA bakterií; Humans; pulzní gelová elektroforéza; DNA fingerprinting; DNA Fingerprinting; Agriculture; Molecular Epidemiology; mikrobiální testy citlivosti; Cluster Analysis; Phenotype; Electrophoresis, Gel, Pulsed-Field; Genotype; lidé; zvířata; molekulární epidemiologie; mikrobiologie životního prostředí; DNA, Bacterial; Cattle; zemědělství; biofilmy; Environmental Microbiology; Milk; fenotyp; skot; shluková analýza; Bacterial Typing Techniques; genotyp; Animals; mléko; Staphylococcus epidermidis; techniky typizace bakterií; Biofilms